HBV induces different responses of the hepatocytes and oval cells during HBV-related hepatic cirrhosis. (28th February 2019) - Zhang, Lei; Chen, Yan; Zhang, Li-Jun; Wang, Ming; Chang, Dong-Lei; Wan, Wei-Wei; Zhang, Bi-Xiang; Zhang, Wan-Guang; Chen, Xiao-Ping
Abstract: Although hepatitis B virus (HBV)-related cirrhosis and hepatocellular carcinoma (HCC) cause a sever health problem worldwide, the underlying mechanisms are still elusive. This study aimed to investigate the responses of different cell types isolated from HBV transgenic mice. A cross-sectional set of hepatocytes and oval cells were obtained from HBV transgenic and control mice. Flow cytometry, immunohistochemistry and microarray were applied to investigate the cell biology of the hepatocytes and oval cells. Our results showed that HBV induced the proliferation of both cell oval cells and hepatocytes, and induced cell death of HBV hepatocytes while had minimal effects on oval cells. Further molecular and pathways analysis identified some genes and signaling pathways may be responsible for the different responses between oval cells and hepatocytes. In addition, analyses of selectively ten genes by IHC staining in human samples were consistent with microarray data. In summary, HBV transgenic mice is a useful model for studying the biological behaviors of oval cells affected by HBV and HBV-cirrhosis. Also, our results help better understand the mechanisms of HBV induced cirrhosis, and provide novel progenitor markers or prognostic/therapeutic markers. Highlights: HBV induced proliferation of both hepatocytes and oval cells, and induces cell death of hepatocytes. HBV expression induced cell death in HBV hepatocytes, but had minimal effects on oval cells. HBV expression affects a significantly larger number of genes and signaling pathways in oval cells than in hepatocytes. These genes and pathways might be new progenitor markers and play roles in HBV-related stem/progenitor-derived HCC.